Kingdom of Swaziland : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This paper highlights that banks and nonbank financial institutions, businesses and households have large exposures to the government and, in some cases, their own vulnerabilities. In this context, a fiscal shock can rapidly propagate into the economy through the financial sector. The financial sector is also likely to amplify the impact of shocks on the economy, possibly opening the way to deep recession. In the case of an extreme shock with difficulties in servicing debt, the banking system capitalization would be significantly hit. Staff analysis highlights the need for fiscal consolidation and for strengthening the CBS's role in monitoring and managing macrofinancial risks. Since 2015, the government's balance sheet, liquidity, and risk exposures have been rapidly deteriorating, raising concerns about the impact on other sectors of the economy. As in many countries, the government in Swaziland is a major economic player with strong linkages with both the financial and nonfinancial sectors.